Ex Animo - Academie Beeldende Kunsten Maastricht. - den Adel, Coralie; Bakker, Floortje; Boekraad, Hugues; Bär, N.M.; Cobben, Math; Feringa, Marieke; Geene, Theo; Harberink, Gertjan; Hoet, Roy; Huyts, Steijn; Lebbink, Gusta; Lemmen, Hans; et al. (Maastricht : Academie Beeldende Kunsten, 1997)
Camps, Barry ; Emmerich, Hadassah ; Frank, Tamar ; Kirkli, Miriam ReedersYonca ; Stienen, Jos ; van Wel, Daan ; Jessen, Jos ; van der Lubben, Claudia ; Nordhausen, Monika ; Kleeman, Christian ; Golvaarts, Gert ; Schoener, Georg ; Wynia, Hiltje ; Rooijakkers, Johan ; Vughts, Fanny ; van Gerwen, Edwin ; Reichert, Jurgen ; van der Eijnden, Mark ; Guthan, Klaus ; Prange, Jean ; Roderburg, Kris ; Technau, Serge ; Brinke, Saïd ten
Nederlands
boek
Keywords: Maastricht